PENGARUH PENERAPAN SISTEM DALAM MENINGKATKAN KINERJA MANAJEMEN RANTAI PASOK PADA PT. CITRA SHIPYARD - Cahyati, Sri Cici Afrida; Thai, Kristina; Jenny, Yang; Susanti, Oktris; Syahara, Elvina; Qadri, Rizni Aulia; Zai, Immanuel (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
In a company, of course, there are ups and downs of a business, one of which isCompany Performance and Supply Chain. The purpose of this analysis is to be able toanalyze the SCM network model that is suitable for a company, and to be able to designan SCM network model for a company. Based on the analysis conducted by the author,no gaps were found that could affect the supply chain and decrease the performancefaced by PT Citra Shipyard. The methodology used is the method of observation anddirect interviews, we made observations to find data from the internet and directinterviews with Citra Shipyard.Keywords: Supply Chain Management, and Enterprise resource planning (ERP)